Types of Invasive Plants and Threats to Animal Conservation in National Park - Putra, Bagus Susilo (Jurnal Natur Indonesia, 2022)
Invasive plants are plants that can interfere with other plant life because invasive plants use competition and harm the host they live on. Animal conservation is currently the focus of research so that biodiversity is always maintained in the National Park such as mantangan (Merremia peltata (L.) Merr.) Chromolaena odorata (L), Stachtarpheta jamaicensis. Based on the way of life and rapid reproduction of this invasive plant, it disturbs the habitus of other plants in developing so that it can damage the food chain in the National Park. Conservation of animals in National Park must be in line with the conservation of the surrounding ecology so that the natural ecosystems in the National Parks and biodiversity are fully preserved.